HTLV-1 Transmission and HIV Pre-exposure Prophylaxis: A Scoping Review - Bradshaw, Daniel; Taylor, Graham Philip (Frontiers in Medicine, 2022)
HIV pre-exposure prophylaxis (HIV-PrEP) is effective for reducing the likelihood of HIV acquisition in HIV-negative people at high risk of exposure. Guidelines recommend testing for sexually-transmitted infections before starting, and periodically on PrEP, including bacterial infections, HIV, hepatitis C virus and, for those who are non-immune, hepatitis B virus. Diagnosed infections can be promptly treated to reduce onward transmission. HTLV-1 is not mentioned although is predominantly sexually-transmitted and causes adult T cell leukaemia/lymphoma or myelopathy in 10% of those infected and is associated with an increased risk of death in those without any classically HTLV-associated condition. The 2021 WHO Technical Report on HTLV-1 called for strengthening of global public health measures against its spread. In this scoping review, we therefore (1) discuss the epidemiological context of HIV-PrEP and HTLV-1 transmission; (2) present current knowledge of antiretrovirals in relation to HTLV-1 transmission prevention, including nucleos(t)ide reverse transcriptase inhibitors and integrase strand transfer inhibitors (INSTI); (3) identify knowledge gaps where data are urgently required to inform global public health measures to protect HIV-PrEP users from HTLV-1 acquisition. We suggest that systematic seroprevalence studies amongst PrEP-using groups, including men who have sex with men, people who inject drugs and female sex workers, are needed. Further data are required to evaluate antiretroviral efficacy in preventing HTLV-1 transmission from in vitro studies, animal models and clinical cohorts. PrEP delivery programs should consider prioritising the long acting injectable INSTI, cabotegravir, in HTLV-1 endemic settings.